Men’s and Women’s Language Features in Taylor Swift’s Interview with Jimmy Fallon - Vindy Melliany Puspa; Nuraeni, Indah; Almsari, Fuji (Talenta Publisher, 2025)
This study aims to analyze men’s and women’s language features and their functions found in The Tonight Show Starring Jimmy Fallon's episode with Taylor Swift. A qualitative method with a sociolinguistics approach were applied to analyze the data, and to collect the data, the researcher uses the documentation technique. The researcher also utilized Lakoff’s theory of women’s language (2004), Coates’ theory of men’s language (2015), and Jakobson’s theory of language functions (2013) to answer the research problems. The result of this study highlights three main findings. First, there are 80 Jimmy Fallon’s utterances included in men’s language features. It consists of minimal response (38.75%), compliment (28.75%), interruption (17.50%), and command and directive (15%). Second, there are 271 Taylor Swift’s expressions included in women's language features, namely lexical hedge and filler (59.41%), intensifier (16.24%), emphatic stress (13.65%), empty adjective (4.43%), hypercorrect grammar (2.58%), rising intonation on declarative (1.48%), super-polite form (1.11%), question tag (0.74%) and avoidance of strong swear word (0.37%). Third, men’s and women’s language features found in the data serve several functions, namely expressive (72.63%), phatic (10.06%), referential (7.26%), metalinguistic (5.31%), and directive (4.75%). Accordingly, it can be concluded that not all men’s and women’s language feature as well as their language functions found in this study. There is no use of swear, taboo language, and precise color term. There are also no utterances that have a phatic function.